Public Masses Awareness and The Social Responsibility Toward Public Uprising: A sociological approach to a reality of The Iraqi Demonstrations 2019. - Khalid Mahmoud Hamy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Mass awareness is not only a perceptual recognition of reality, but rather is the product of a reciprocal relationship between individual to social grouping willingness, and subjective to objective tendencies, especially the psychological dimensions are primary areas of consciousness formed by individuals. Accordingly, these cognitive domains, the degree to which it reflects social reality is determined. A framework that combines the outcome of the interaction of individuals in social reality, in which individuals’ perceptions and personal feelings are melted into objective facts. Social responsibility is one of the manifestations that embody the moral values of individuals, and thus their contribution to the current movement expressed in the form of popular demonstration. The importance of this study lies in its novelty which investigates one of the topics that were not highlighted before. The current study aims at achieving a set of purposes. The research was based on the inductive analytical method. The study has come up with the following conclusions: 1. This revolution succeeded in the issue of renouncing sectarianism and uniting the ranks of the Iraqi people, changing the patterns of traditional popular loyalty to political symbols and parties dominating power. the masses were relatively liberated from the traditional influence of clans and the religious establishment in calming the situation. This means that the revolution has implicitly surpassed the most prominent elements of social control. 2. This revolution could not sustain and encounter the excessive violence directed against the demonstrators only after awareness was established among the revolutionary masses. The psychological and social motives support and determine their social position towards the surrounding issues. 3. This social revolution has crossed all the red lines that were placed against the protesters. We have also seen direct support from Iraqis abroad.